High-performance carbon dots extraction method based on microwave treatment of pineapple peel
Patent Information
- Application Number
- CN202510421297.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的目的在于克服现有技术中碳点制备方法成本高、工艺复杂、环境负担大的缺陷,提供一种基于菠萝皮废弃物的高效、绿色碳点提取方法
(1)绿色高效:以菠萝皮为原料,实现废弃资源的增值利用;微波辅助碳化工艺反应时间短30分钟以上,能耗降低40%以上。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0002] This invention belongs to the field of materials science and environmental technology, specifically relating to a high-performance carbon dot extraction method based on microwave treatment of pineapple peel, and more particularly to a green technology for preparing high-performance carbon dots from biomass waste (pineapple peel) through microwave-assisted carbonization, resolution, alcohol precipitation and purification processes. Background Technology
[0003] Pineapple peels are a major waste product generated during pineapple processing. Rich in cellulose, hemicellulose, lignin, and polyphenolic compounds, they possess potential value as a biomass carbon source. Carbon dots (CDs), as a novel nanomaterial, show broad application prospects in fields such as bioimaging, environmental monitoring, and photocatalysis due to their excellent optical properties, low toxicity, and biocompatibility. Traditional carbon dot preparation methods often rely on chemical precursors or complex processes, resulting in high raw material costs, cumbersome processes, the use of toxic reagents, and environmental pollution. In recent years, biomass waste has been increasingly explored as a green carbon source for carbon dots due to its renewability and low cost. However, existing technologies generally suffer from low carbonization efficiency, uneven product particle size, and low fluorescence quantum yield.
[0004] In existing biomass carbon dot preparation technologies, the hydrothermal method requires a long-term, high-temperature, and high-pressure reaction of 6-24 hours, resulting in high energy consumption and unstable yields. The chemical oxidation method requires strong acids or bases, leading to complex subsequent purification steps and the potential for harmful residues. Furthermore, existing methods have stringent requirements for raw material pretreatment; parameters such as particle size and carbonization temperature have not been effectively optimized, limiting the efficient conversion of biomass waste and failing to meet practical application needs.
[0005] Microwave-assisted carbonization technology has been explored for carbon dot preparation due to its advantages such as rapid heating, high energy efficiency, and controllable reaction conditions. However, existing microwave processes often focus on optimizing single parameters such as power or time, lacking systematic design for raw material pretreatment, solvent systems, and purification processes. This results in insufficient product purity and the absence of functional groups. For example, microwave methods reported in the literature often require the addition of surface modifiers to improve carbon dot performance, but the introduction of additional chemical reagents increases the environmental burden and may affect the biocompatibility of the materials.
[0006] In summary, existing methods for extracting carbon dots from biomass waste generally suffer from problems such as complex processes, high costs, and insufficient product performance. Therefore, there is an urgent need to develop a green, efficient, and simplified carbon dot extraction technology that can fully utilize waste resources such as pineapple peels, while simultaneously achieving large-scale preparation of high-fluorescence carbon dots to meet the application needs of environmental, biomedical, and other fields. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing carbon dot preparation methods, such as high cost, complex processes, and heavy environmental impact, and to provide a highly efficient and green carbon dot extraction method based on pineapple peel waste. By optimizing the microwave-assisted carbonization process and multi-step purification technology, high-performance carbon dot preparation and large-scale carbon dot preparation are achieved, while reducing raw material costs and environmental pollution.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A high-performance carbon dot extraction method based on pineapple peel includes the following steps: (1) Pretreatment: Wash and dry the pineapple peel and then crush it to 100 mesh; (2) Microwave carbonization: Take 1g of crushed pineapple peel, add 5-10mL of deionized water, mix, place in a microwave reactor, and react under certain temperature conditions; (3) Reconstitution and purification: After cooling the reaction product, dissolve it in deionized water, filter it, add ethanol solution to precipitate impurities, and collect the supernatant by centrifugation; (4) Concentration and dialysis: Concentrate by vacuum rotary evaporation, and then remove small molecule impurities by using a dialysis membrane of a certain size; (5) Drying: Dry the concentrated carbon dot solution in an oven or freeze dry to obtain solid carbon dot powder.
[0010] Preferably, the drying in step (1) is vacuum drying, the temperature is 40-60℃, and the drying time is 18-24 hours.
[0011] Preferably, in step (2), 1g of pineapple peel is added to 5-10mL of deionized water, the microwave reaction power is 600-800W, and the reaction time is 3-10 minutes.
[0012] Preferably, in step (3), the concentration of the ethanol solution is 95% and the centrifugation speed is 5000 rpm.
[0013] Preferably, the temperature of vacuum rotary evaporation in step (4) is 40-60°C, the size of the dialysis bag is 1000 Da, and the dialysis time is 24-48 hours.
[0014] The beneficial effects of this invention are: (1) Green and efficient: Using pineapple peel as raw material, the waste resources are utilized with added value; the microwave-assisted carbonization process has a short reaction time of more than 30 minutes and reduces energy consumption by more than 40%. (2) Simplified process: The traditional acid / base purification steps are replaced by the resolution-alcohol precipitation combined technology, which reduces the use of chemical reagents and improves the purification efficiency by 30%. (3) Wide range of applications: Carbon dots can be applied to fields such as bioimaging, fluorescence detection of environmental pollutants, photocatalytic degradation and flexible electronic devices. (4) Innovation: For the first time, microwave-assisted carbonization technology is combined with pineapple peel waste to achieve low-cost, high-purity green synthesis of carbon dots. By optimizing the resolution solvent system and alcohol precipitation parameters, the purity and fluorescence performance of carbon dots are significantly improved, and the introduction of toxic modifiers is avoided.
[0015] Carbon dots were extracted and their properties were analyzed.
[0016] 1. Experimental Materials and Instruments 1.1 Experimental Materials The pineapple peels used in this experiment come from Hainan Island, which has a tropical monsoon climate, early spring, rapid temperature rise, large daily temperature difference, long summer and no winter, and abundant sunshine and warmth. It is known as a "natural greenhouse".
[0017] 1.2 Test Reagents The reagents used in this invention are shown in Table 1.
[0018] Table 1 Main reagents used in the experiment 1.3 Instruments The experimental instruments used in this invention are shown in Table 2. Table 2. Experimental Instruments
[0019] 2. Sensory evaluation indicators and scoring criteria
[0020] To assess the effectiveness of carbon dot preservation, a sensory evaluation of strawberry preservation was conducted. 2.1 Color and appearance, see Table 3. Table 3 Scoring Criteria for Color and Appearance 2.2 Odor, see Table 4. Table 4. Smell Scoring Criteria 2.3 Texture, see Table 5. Table 5. Texture Scoring Criteria To reduce errors and ensure the accuracy of sensory evaluation scores in the experiment, the sensory evaluators participating in the experiment of this invention were randomly selected from people with rich experience in sensory evaluation in this field. The group consisted of students and teachers, with a total of 5 people. As shown in the table above, the evaluation score of strawberry freshness was divided into three items, each accounting for 20 points. The average score and the sum of the average scores were used as the final evaluation result of the product.
[0021] 3. Carbon dot extraction and preparation steps (1) Preprocessing Rinse the fresh pineapple peel three times with deionized water to remove surface impurities, dry it in a dehydrator at 45℃ for 36 hours, and then grind it to 100 mesh. (2) Microwave carbonization The crushed pineapple peel was mixed with deionized water at a mass-to-volume ratio of 1:5 (g / mL), transferred to a microwave reactor, and the microwave power was set to 800W for 2 minutes. After the reaction was complete, the mixture was allowed to cool naturally to room temperature. (3) Resolution and alcohol precipitation Mix the microwave carbonization product with deionized water at a volume ratio of 1:8, filter, add 3 times the volume of 95% ethanol solution to the supernatant, mix well, centrifuge at 5000 rpm for 15 minutes, and collect the supernatant. (4) Concentration and purification The supernatant was concentrated in a vacuum rotary evaporator at a temperature of 55°C and a vacuum of 0.08 MPa until it was reduced to 1 / 10 of its original volume. The supernatant was then placed in a dialysis bag with a molecular weight cutoff of 1000 Da and dialyzed in deionized water for 36 hours (with the water changed every 6 hours). (5) Drying The concentrated carbon dot solution was transferred to a blower dryer and dried at 40°C for 24 hours to obtain a pale yellow solid carbon dot powder.
[0022] 4. Determination of carbon point properties
[0023] 4.1 Fluorescence performance determination (1) Sample preparation Take the dried solid carbon dot powder, dissolve it in deionized water, and prepare a carbon dot solution of a certain concentration. (2) Instrument setup and calibration Start the instrument and allow it to warm up for 30 minutes until it reaches a stable state. Set the excitation wavelength (Ex) to 466 nm and the emission wavelength (Em) to a scanning range of 480-700 nm. Set the PMT voltage to 700 V, the scanning speed to 3317-3332 nm / min, and the slit width to 5 nm for both excitation and emission. (3) Baseline calibration Use deionized water for blank scanning to subtract background signals. (4) Fluorescence spectroscopy determination Inject the carbon dot solution into a quartz cuvette, avoiding the formation of air bubbles, place it in the sample chamber, start the scan, record the emission spectrum curve, and determine the maximum emission wavelength (e.g., 450 nm) and the corresponding fluorescence intensity. (5) Data processing is shown in Table 6. Table 6. Conclusions on Fluorescence (6) Conclusion: Carbon dots exhibit significant blue-green emission under 466nm excitation, with peak wavelengths concentrated at 490nm.
[0024] 4.2 Determination of antioxidant properties
[0025] Determination of DPPH radical scavenging rate by carbon dots Experimental steps: 4.2.1 Preparation of DPPH free radical solution Accurately weigh 25 mg of DPPH powder and dissolve it in 100 mL of anhydrous ethanol to prepare a 0.25 mg / mL (approximately 0.1 mM) DPPH stock solution. Before use, dilute to a wavelength of 517 nm and measure the absorbance to be 0.70 ± 0.02 to ensure the stability of the solution activity. 4.2.2 Preparation of carbon dot sample solution Take the dried pineapple peel carbon dot powder, dissolve it in deionized water, and prepare a 1.0 mg / mL stock solution; Gradient dilution: To prepare a solution of 0.5 mg / mL: take 1 mL of stock solution + 1 mL of deionized water; To prepare a solution of 0.2 mg / mL: take 1 mL of stock solution + 4 mL of deionized water; To prepare 0.1 mg / mL solution: take 1 mL of stock solution + 9 mL of deionized water. 4.2.3 Construction of the reaction system (1) Experimental group: Take 1 mL of DPPH solution and 1 mL of carbon dot solution and mix them in a light-protected centrifuge tube; (2) Blank group: Mix 1 mL of DPPH solution with 1 mL of deionized water; (3) Background group: Mix 1 mL of anhydrous ethanol with 1 mL of carbon dot solution; (4) After mixing evenly, let it stand at 25°C for 30 minutes in the dark. 4.2.4 Absorbance Measurement (1) Transfer the reaction solution to a cuvette; (2) Using anhydrous ethanol as a reference, the absorbance at 517 nm was measured: A0: Absorbance of blank group (DPPH mixed with water) A1: Absorbance of the experimental group (mixture of carbon dot solution and DPPH) A2: Background absorbance (carbon dots mixed with water) 4.2.5 Calculation of Free Radical Scavenging Rate 4.2.6 Results Analysis Each experiment was repeated three times. The absorbance results of the carbon dots are shown in Tables 7, 8, 9, and 10. Table 7 Absorbance of 1.0 mg / mL carbon dots Table 8 Absorbance of 0.5 mg / mL carbon dots Table 9 Absorbance of 0.2 mg / mL carbon dots Table 10 Absorbance of 0.1 mg / mL carbon dots According to the data... The average DPPH scavenging rate of carbon dots is shown in Table 11. Table 11 Average DPPH scavenging rate of carbon dots
[0026] Determination of the ABTS radical scavenging rate of carbon dots Experimental steps: 4.2.7 Preparation of ABTS Free Radical Solution Mix 7 mmol ABTS solution with an equal volume of 2.45 mmol potassium persulfate solution, and let stand at room temperature for 16 hours in the dark to generate ABTS. + Free radical stock solution; dilute with PBS buffer (pH 7.4) to an absorbance of 0.70 ± 0.02 at 734 nm before use. 4.2.8 Preparation of carbon dot sample solution Take the dried pineapple peel carbon dot powder, dissolve it in deionized water, and prepare a 1.0 mg / mL stock solution; Gradient dilution: To prepare a solution of 0.5 mg / mL: take 1 mL of stock solution + 1 mL of deionized water; To prepare a solution of 0.2 mg / mL: take 1 mL of stock solution + 4 mL of deionized water; To prepare 0.1 mg / mL solution: take 1 mL of stock solution + 9 mL of deionized water. 4.2.9 Construction of the reaction system (1) Experimental group: Take 1 mL of ABTS solution and 1 mL of carbon dot solution and mix them in a light-protected centrifuge tube; (2) Blank group: Mix 1 mL of ABTS solution with 1 mL of PBS buffer; (3) Background group: Mix 1 mL of PBS buffer with 1 mL of carbon dot solution; (4) After mixing evenly, let it stand at 25°C for 30 minutes in the dark. 4.2.10 Absorbance Measurement (1) Transfer the reaction solution to a cuvette; (2) Using PBS buffer as a reference, the absorbance at 734 nm was measured: A0: Absorbance of the blank control group (ABTS mixed with PBS buffer) A1: Absorbance of the experimental group (mixture of carbon dot solution and ABTS) A2: Background absorbance (carbon dots mixed with PBS buffer) 4.2.11 Calculation of Free Radical Scavenging Rate 4.2.12 Results Analysis Each experiment was conducted three times, and the absorbance results of the carbon dots are shown in Tables 12, 13, 14, and 15. Table 12 Absorbance of 1.0 mg / mL carbon dots Table 13 Absorbance of 0.5 mg / mL carbon dots Table 14 Absorbance of 0.2 mg / mL carbon dots Table 15 Absorbance of 0.1 mg / mL carbon dots According to the data: The average removal rate of ABTS by carbon dots is shown in Table 16. Table 16 Average ABTS removal rate of carbon dots
[0027] Summary of antioxidant properties: Based on DPPH and ABTS free radical scavenging experimental data, the carbon dots extracted from pineapple peel exhibited excellent antioxidant properties. The specific conclusions are as follows: (1) Highly efficient free radical scavenging ability: The antioxidant activity of carbon dots was positively correlated with concentration. In the ABTS and DPPH experiments, the scavenging rate increased significantly with increasing concentration. At a concentration of 1.0 mg / mL, carbon dots achieved scavenging rates of 95.57% and 90.06% for ABTS and DPPH free radicals, respectively, approaching complete neutralization levels, indicating that they possess significant and rapid free radical scavenging capabilities. (2) Broad-spectrum antioxidant properties: Carbon dots showed excellent performance in different free radical models (DPPH and ABTS), indicating that their antioxidant activity has a broad spectrum and can adapt to a variety of oxidative stress environments. The surface is rich in functional groups such as hydroxyl (-OH) and carboxyl (-COOH), which may enhance the free radical scavenging ability through electron transfer or hydrogen atom donation mechanisms. 4.3 Determination of Freshness
[0028] Determination of strawberry weight loss rate Experimental steps: (1) Prepare carbon dot solutions of different concentrations: 1.0 mg / mL; 0.5 mg / mL; 0.2 mg / mL; 0.1 mg / mL. The preparation method is the same as above. (2) Group design: Experimental group: Carbon dot solution of different concentrations was sprayed to verify its preservation effect. Control group: Distilled water was sprayed to eliminate the influence of the physical operation of "spraying liquid" on the results. Blank control group: Strawberries were stored directly without any spraying treatment and were used to compare the differences between strawberries in their natural state and the treated group. (3) Select 5 strawberries of similar variety, maturity and no mechanical damage for each group, divide them into three groups, spray the same volume of liquid on each group of strawberries, and place them at room temperature for 7 days. Weigh their quality changes at a fixed time every day. (4) Calculate the daily weight loss rate and the total weight loss rate. (5) Analysis of experimental results, see Table 17. Table 17 Average weight loss rate of strawberries (6) Conclusion: Carbon dot spraying effectively inhibits strawberry water evaporation and metabolic activity, and can prolong the shelf life.
[0029] pH measurement Experimental steps: (1) Group design: Divide into 3 groups, and repeat the experiment 3 times in each group; Experimental group: 5 strawberries, with a carbon dot solution of 1.0 mg / mL evenly sprayed on their surface; Control group: 5 strawberries, with an equal amount of distilled water evenly sprayed on their surface; Blank group: 5 strawberries, without any treatment. (2) pH measurement procedure: Select 5 strawberries from each group at regular intervals every day, weigh 10g of strawberry pulp, add 50mL of deionized water, mix well to make a homogenate. (3) pH meter calibration: Calibrate with pH 7.00 buffer solution, immerse the electrode below the liquid surface, and confirm after the reading stabilizes. (4) Sample determination: Each sample shall be determined at least 3 times and the average value shall be taken. (5) Analysis of experimental results, see Table 18. Table 18 Average pH of Strawberries (6) Conclusion: Carbon dots on pineapple peel effectively maintain the acidic environment of strawberries by inhibiting microbial activity or delaying the decomposition of organic acids, thereby extending the shelf life.
[0030] Sensory evaluation conclusions on strawberry preservation Experimental grouping and scoring results: According to the sensory evaluation criteria (color and appearance, smell, texture, each item with a full score of 20 points), the sensory scores of the six groups of treated strawberries are as follows, see Table 19. Table 19 Sensory Evaluation Scores of Strawberries
[0031] Conclusion Analysis: (1) Best preservation effect: The 1.0 mg / mL carbon dot group was significantly better than other groups with a total score of 51.5. Its color was bright, its aroma was close to that of natural strawberries, and its texture was firm, indicating that high concentration carbon dot solution can effectively inhibit browning, delay spoilage and maintain the elasticity of fruit flesh. (2) Concentration dependence: The carbon dot concentration was positively correlated with the preservation effect. The 0.5 mg / mL group was the second best, and the preservation effects of the 0.2 mg / mL and 0.1 mg / mL groups decreased in that order, but were still better than the distilled water group and the untreated group, indicating that even low concentrations of carbon dots have a certain preservation effect. (3) The blank control group showed the lowest score. The strawberries were severely browned, had a noticeable off-odor, and softened in texture, which verified the rapid decay process of strawberries under natural conditions. (4) Comparison of distilled water group: The distilled water group was slightly better than the untreated group, possibly because the surface wetness temporarily delayed dehydration, but could not inhibit microbial activity, and was ultimately significantly worse than the carbon dot treatment group.
[0032] Writing Instructions: (1) Technical rigor: Multiple implementation verifications have demonstrated that the carbon dots extracted from pineapple peel by microwave method have good performance. (2) Data support: Supplement data such as response surface optimization, batch repeatability, and stability comparison to enhance persuasiveness. (3) Differentiated layout: highlight the full utilization of waste and innovative agricultural applications, and avoid the patent barriers of competitors. Attached Figure Description Figure 1 This is a graph showing the DPPH free radical scavenging rate of carbon dots at different concentrations; Figure 2 This is a graph showing the ABTS radical scavenging rate of carbon dots at different concentrations; Figure 3 This is a graph showing the average weight loss rate of strawberries treated with different concentrations of carbon dots. Figure 4 This is a graph showing the effect of carbon dots on the pH of strawberries.
Claims
1. A high-performance carbon dot extraction method based on microwave-treated pineapple peel, characterized in that, Includes the following steps: (1) Pretreatment: Wash and dry the pineapple peel and then crush it to 80-120 mesh; (2) Microwave carbonization: Take 1g of crushed pineapple peel, add 5-10mL of deionized water, place it in a microwave reactor, and react for 3-10 minutes at 600-800W power. (3) Reconstitution and purification: Dissolve the microwave carbonization product in deionized water, filter it, add 90-95% ethanol solution for precipitation, centrifuge at 4000-6000 rpm to remove impurities and collect the supernatant. (4) Concentration and dialysis: The supernatant was concentrated to 1 / 5-1 / 10 of its original volume by vacuum rotary evaporation, and then purified by dialysis using a dialysis membrane with a molecular weight cutoff of 500-2000 Da. (5) Drying: The purified carbon dot solution is dried to obtain solid carbon dot powder.
2. The method according to claim 1, characterized in that, The drying process described in step (1) involves a temperature of 40-60℃ and a drying time of 18-24 hours.
3. The method according to claim 1, characterized in that, The microwave reaction temperature in step (2) is 100-150℃, and the reaction pressure is atmospheric pressure.
4. The method according to claim 1, characterized in that, In step (3), the amount of ethanol solution added is 2-4 times the volume of the supernatant, the centrifugation speed is 4500-5500 rpm, and the centrifugation time is 10-20 minutes.
5. The method according to claim 1, characterized in that, The temperature of the vacuum rotary evaporation in step (4) is 40-60℃, the vacuum degree is 0.06-0.10MPa, the dialysis time is 24-48 hours, and the deionized water is replaced every 4-8 hours during the dialysis process.
6. The method according to claim 1, characterized in that, The drying process described in step (5) is either blower drying or freeze drying. The blower drying temperature is 35-45℃, and the freeze drying temperature is -40 to -50℃.
7. The carbon dots prepared by the method according to any one of claims 1-6, characterized in that, The carbon dots have a fluorescence quantum yield of 1-3%, a particle size distribution of 2-10 nm, and contain hydroxyl, carboxyl, and amino functional groups on their surface.
8. The carbon dot according to claim 7, characterized in that, Its antioxidant properties meet at least one of the following: (1) At a concentration of 1.0 mg / mL, the scavenging rate of DPPH free radicals is ≥90%; (2) The scavenging rate of ABTS free radicals at a concentration of 1.0 mg / mL is ≥95%.
9. The application of the carbon dots according to claim 7 in bioimaging, fluorescence detection of environmental pollutants, photocatalytic degradation, or food preservation.
10. A method for preserving strawberries, characterized in that, The carbon dots described in any one of claims 7-8 are prepared into an aqueous solution of 0.1-1.0 mg / mL and sprayed onto the surface of strawberries to form a protective film. The preservation method results in less weight loss and better maintenance of pH value compared to spraying water or no treatment.